Electromagnetic interference measurement for axle counters light rapid transit railway in Indonesia - Yudhistira Yudhistira; Yoppy Yoppy; Elvina Trivida; Tyas Ari Wahyu Wijanarko; Hutomo Wahyu Nugroho; Dwi Mandaris (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The measurement and analysis of electromagnetic interference (EMI) from light rapid transit (LRT) axle counters against magnetic field interference in Indonesia has been carried out. The low-cost magnetic sensors were developed according to the British Standard (BS) EN 50592:2016. The measurement setup and magnetic field limit were based on the British Standard EN 50592:2016 and ERA/ERTMS/033281 standard. Two frequency range of the measurements, lower and higher frequencies with two different train running mode, acceleration mode and deceleration mode were applied in this research. The results in lower frequency range (10 to 100 kHz) were very close to the limit value in both acceleration and deceleration mode, especially at the 30 to 50 kHz for the y and z directions. Although there may possibly magnetic interference at low frequencies, most of the magnetic field emissions were still in acceptable range.